(untitled) (European Journal of Natural Sciences and Medicine, 2021)
The idea of graphing what is called the lead-tin eutectic point when alloys are produced from elemental lead and tin metals may be very common and established in chemistry and materials science laboratories. Producing art medals from the alloys that are made in such experiments is decidedly not. We will present how the lead-tin eutectic experiment can be performed in the chemistry lab, and how graphite blocks can be used as both mold and heat sink for the creation of art medals, utilizing metal alloys produced by students in the laboratory. The process brings together art, science and engineering in a single experience. We conclude that this has been found to be beneficial for students, yet is a technique that can be utilized by virtually any person who wishes to experiment and create with low-melting metal alloys.